Variedades de abóboras (Cucurbita moschata) agronomicamente superiores e com altos teores de carotenoides via seleção participativa - Gomes, Aline Batista Belem (2021)
The concern with the growing increase in malnutrition in the world led to the development of studies on food biofortification, with the intention of improving the quality of agricultural products through plant improvement. Pumpkin is considered an important source of carotenoids, mainly β-carotene, a precursor of vitamin “A”. This research aimed to estimate the divergence and the genetic parameters in pumpkin progenies selected for fruit and nutritional chemical variables, submitted to different cycles of Massal Participatory Selection. An experiment was conducted at the Experimental Field of Embrapa Tabuleiros Costeiros, located in the municipality of Frei Paulo-SE. The experiment consisted of eight treatments, referring to seven successive cycles of Participatory Mass Selection (C1, C2, C3, C4, C5, C6, C7) and a control (commercial variety, Abóbora Maranhão). There was a direct genetic gain for the total carotenoids content with potential for indirect gains in dry mass and soluble solids content, throughout the Participatory Mass Selection cycles. The C6 selection cycle added more superior progenies for total carotenoids. It is also worth noting that the pumpkin fruits from the C6 population maintained morphological characteristics similar to the commercial variety.